Parasit Gastrointestinal pada Kadal Naga Berjanggut (Pogona vitticeps) di Cijeruk, Bogor - Nisrina Rosyida Noor Rifai; Arifin Budiman Nugraha; Ekowati Handharyani; Fajar Kawitan; Umi Cahyaningsih (Jurnal Sain Veteriner, 2023)
Bearded dragons are reptiles that are quite popular as pets. There are many factors of disease that can infect bearded dragons. The environment and feed affect the level of disease threat, such as parasitic infection in the gastrointestinal tract. Data information related to parasitic gastrointestinal infections in bearded dragons in Indonesia is still limited, so supporting examinations are necessary to help diagnose. A total of 38 fecal samples were collected from the bearded dragon in Cijeruk Bogor. Samples were examined by simple flotation method, Ziehl Neelsen staining, and counting the number of parasitic eggs. All samples were positive for gastrointestinal parasite infections such as Choleoeimeria sp., Isospora amphiboluri, Cryptosporidium spp., ascarid egg, and oxyurid egg. The average number of Choleoeimeria sp. and Isospora amphiboluri oocysts were 8730 and 51.281 oocysts per gram of feces. The average number of helminth eggs per gram was 290 and 2325 for ascarid and oxyurid, respectively. Most of the infected bearded dragons do not show significant clinical symptoms. The number of oocysts and worm eggs per gram of feces showed mild and high results.